Flexural Creep Behaviour of Pultruded GFRP Composites Cross-Arm: A Comparative Study on the Effects of Stacking Sequence - Alhayek A.; Syamsir A.; Supian A.B.M.; Usman F.; Asyraf M.R.M.; Atiqah M.A. (MDPI, 2023)
Bending (forming); Bending tests; Creep; Fiber reinforced plastics; Glass fibers; Pultrusion; Reinforcement; Bending creep; Comparatives studies; Creep behaviors; Cross arm; Flexural; Four-point-bending; GFRP composites; Glass-fiber reinforced polymer composites; Glassfiber reinforced polymers (GFRP); Stacking sequence; Bending strength